Atomically dispersed Fe–N–C decorated with Pt-alloy core–shell nanoparticles for improved activity and durability towards oxygen reduction. Issue 9 (6th August 2020) - Ao, Xiang; Zhang, Wei; Zhao, Bote; Ding, Yong; Nam, Gyutae; Soule, Luke; Abdelhafiz, Ali; Wang, Chundong; Liu, Meilin
Abstract : An efficient, stable, and cost-effective ORR catalyst composed of core–shell Pt-alloy and non-Pt-group-metal single atoms is reported for PEMFCs. Abstract : One of the key challenges that hinders broad commercialization of proton exchange membrane fuel cells is the high cost and inadequate performance of the catalysts for the oxygen reduction reaction (ORR). Here we report a composite ORR catalyst consisting of ordered intermetallic Pt-alloy nanoparticles attached to an N-doped carbon substrate with atomically dispersed Fe–N–C sites, demonstrating substantially enhanced catalytic activity and durability, achieving a half-wave potential of 0.923 V ( vs. RHE) and negligible activity loss after 5000 cycles of an accelerated durability test. The composite catalyst is prepared by deposition of Pt nanoparticles on an N-doped carbon substrate with atomically dispersed Fe–N–C sites derived from a metal–organic framework and subsequent thermal treatment. The latter results in the formation of core–shell structured Pt-alloy nanoparticles with ordered intermetallic Pt3 M (M = Fe and Zn) as the core and Pt atoms on the shell surface, which is beneficial to both the ORR activity and stability. The presence of Fe in the porous Fe–N–C substrate not only provides more active sites for the ORR but also effectively enhances the durability of the composite catalyst. The observed enhancement in performance is attributed mainly to the unique structure of the composite catalyst, as confirmed by experimental measurements and computational analyses. Furthermore, a fuel cell constructed using the as-developed ORR catalyst demonstrates a peak power density of 1.31 W cm −2 . The strategy developed in this work is applicable to the development of composite catalysts for other electrocatalytic reactions.